Web-Based Sales Information System Design at Ulos Shop - Hasibuan, Eka Hayana (Cattleya Darmaya Fortuna, 2021)
Ulos Shop is an e-store that is engaged in styles ranging from clothing, bags, shoes, accessories and others, which still require regional expansion in the sale and marketing of products provided both for customers within the city of Medan and outside Medan. Currently, the promotion of products sold on Ulos Shop is only done using Facebook and the recording of transactions at this store is also still manual, allowing errors in recording and also allowing data loss. At this time the way of purchasing at the Ulos Shop store is that customers go directly to the store to view and order the products provided. By building a web-based sales information system on Ulos Shop, it can help stores and customers in making buying and selling transactions, it can also help companies promote products through the internet. The design method uses DFD (Data Flow Diagram) modeling and the creation of a web-based sales system using CMS (Content Management System), namely Opencart. The results of this study are in the form of designing a web-based sales system that can be implemented properly by the company in order to promote products and make buying and selling transactions easily to customers.